Arching Action Revisited - Janas, M.; Sokół-Supel, J.; Supel, J. (Engineering Transactions, 1997)
Reinforced concrete and elastic-tensionless strips transversally loaded and restrained against longitudinal displacements at supports are considered. The support restraints induce important axial forces and that results in a highly nonlinear and unstable character of the structure response. A commercial FEM code is used and the results are compared with those obtained from an approximate approach based upon the post-yield methodology, proposed years ago by the authors. The latter approach neglects elastic flexural deformations but accounts for axial compliance of the system and furnishes simple analytical expressions for the load vs. displacement relations. It appears from the FEM analysis that the flexural compliance has a negligible impact on the peak-load behaviour. The approximate approach gives satisfactory results, when compliance moduli for the structure and for restraining walls are appropriately chosen. Benchmark cases considered allowed for a proposition concerning determination of these moduli.